Upconversion Properties of La2(MoO4)3:Er3+/Yb3+ Green Phosphors Synthesized by Cyclic Microwave-Modified Sol-Gel Method - Sung Lim, Chang (Asian Journal of Chemistry, 2015)
Upconversion La2-x(MoO4)3:Eu3+/Yb3+ phosphors with doping concentrations of Er3+ and Yb3+ (x = Er3+ + Yb3+, Er3+ = 0.05, 0.1, 0.2 and Yb3+ = 0.2, 0.45) were successfully synthesized by the cyclic microwave-assisted sol-gel process and the upconversion photoluminescence properties have been investigated. Well-crystallized particles, formed after heat-treatment at 900 °C for 16 h, showed a fine and homogeneous morphology with particle sizes of 1-5 μm. Under excitation at 980 nm, La1.7(MoO4)3:Er0.1Yb0.2 and La1.5(MoO4)3:Er0.05Yb0.45 particles exhibited a strong 525 nm emission band, a weak 550 nm emission band in the green region and a very weak 655 nm emission band in the red region. The Raman spectra of the particles indicated the presence of weak peaks at lower frequencies induced by the disorder of the [MoO4]2- groups with the incorporation of the Er3+ and Yb3+ elements into the crystal lattice or by a new phase formation.